Sosialisasi Teknis Tata Cara Pelaporan SPT Tahunan PPH Orang Pribadi pada ASN Dan PJLP di Kelurahan Kota Bambu Selatan - Ibraham, Diki; Hasanah, Nurul; Ulfa, Nurul; Rahmawati, Rahmawati; Rokhmawati, Siti Wulan; Suripto, Suripto (BUDGETING : Journal of Business, Management and Accounting, 2024)
The result of this community service activity is the improvement of participants' understanding and skills, especially civil servants (ASN) and contract workers (PJLP) in the South Kota Bambu sub-district, in reporting the Annual Income Tax Return (SPT) of individual taxpayers through E-Filing. The training materials delivered practically and interactively successfully addressed the challenges faced by the participants. Evaluation shows that this activity has a positive impact in enhancing knowledge and understanding related to taxation. Keywords: ASN and PJLP, Kota Bambu Selatan Subdistrict, Reporting of Annual Income Tax Returns.